Overview of training research with loading in unstable conditions - Marinkovic, M.; Ilic, I.; Vukicevic, V. (Sports Science and Health, 2019)
The main goal of this research was to review the works that dealt with the effects of strength training in unstable conditions. A transparent survey covered 24 papers that were not older than 10 years. The sample of respondents are young and middle age groups due to similar abilities. Out of 24 papers: 16 papers were with one group in the experiment, 6 papers were with two groups in the experiment and 2 with three groups in the experiment. After the involvement of the musculature: 9 papers treated pectoral musculature, in 10 papers the involvement of the muscles of the lower limbs was processed, 6 papers dealt with the aspect of engaging the back musculature and the same abdomen, 8 papers treated chest musculature and two papers included shoulder musculature in their research. There was no difference in the degrees of promotion on the basis of gender in the articles. The statistical effect of exercise on unstable substrates was expressed in 13 studies, there were no statistically significant effects in 7 studies, while the same effect of the effects achieved by strength exercises on unstable and stable surfaces was found in 4 papers. The work done primarily suggests a positive effect of exercise on unstable substrates in untrained individuals.